"Where were you so long?": From Meaning to Being in the Mother-imago in Jibanananda Das's "Banalata Sen". Issue 1 (2nd January 2022) - Das, Biswarup
ABSTRACT: In the light of Lacanian dichotomy of "Being" and "Meaning, " the present article intends to illuminate how the protagonist's journey of life in Jibanananda Das's masterwork "Banalata Sen" (1942) proves to be a retreat to the Jungian "mother-imago." This "imago" is the idealized image of the mother constituted by one's infantile memory of her fulfilling self that remains preserved in the unconscious. It imbibes all the facets of womanhood. In essence, it is both instinctual and archetypal. The protagonist's enterprising career in the human world invites into his life a sense of fatigue. He feels disintegrated into sundry worldly roles. The unconscious nostalgia for the unified "Being" eventually transmutes his aimless wanderings in the way of the world to a quest for love and fulfillment. Ultimately he succeeds in recapturing his defragmented entity, his "particular me, " as well as experiencing a sense of blissful serenity through his association with his "mother-imago, " Banalata Sen.